MERUMUSKAN PRINSIP-PRINSIP DAN KRITERIA EKOWISATA DAERAH BALI - Anak Agung Gde Raka Dalem (Environmental Research Center (PPLH) of Udayana University)
Principles and criteria of ecotourism were set by running a workshop on ecotourism trainingin Sanur, Bali, between September 3-5, 2002, involving participants from a wide range ofbackgrounds: government, tourism industry, academics, and NGOs. The workshop was aimed to setup the principles and criteria which is suitable for Bali. Principles of ecotourism as output of theworkshops are as follows: (1) Have a concern, commitment, and responsibility to conservation ofnature and culture; (2) Provide an interpretation which make tourists possible to enjoy nature andfoster their interest on conserving nature; (3) Continuously provide contribution to local communityas well as empowering local community; (4) Sensitive and respect to local socio-culture and localreligious tradition; (5) Abide to law or regulations; (6) Its development must be based on consultationand approved by local community; (7) Continuously provide satisfaction to the costumers/tourists; (8)Honestly and accurately marketed and promoted, so meets tourist’s expectation (responsiblemarketing); (9) Apply harmonious and balanced management based on the Tri Hita Karana concept.Criteria of ecotourism were then formulated based on those principles.